Diversity of Free-Living Environmental Bacteria and Their Interactions With a Bactivorous Amoeba - Brock, Debra A.; Haselkorn, Tamara S.; Garcia, Justine R.; Bashir, Usman; Douglas, Tracy E.; Galloway, Jesse; Brodie, Fisher; Queller, David C.; Strassmann, Joan E. (Frontiers in Cellular and Infection Microbiology, 2018)
A small subset of bacteria in soil interact directly with eukaryotes. Which ones do so can reveal what is important to a eukaryote and how eukaryote defenses might be breached. Soil amoebae are simple eukaryotic organisms and as such could be particularly good for understanding how eukaryote microbiomes originate and are maintained. One such amoeba, Dictyostelium discoideum, has both permanent and temporary associations with bacteria. Here we focus on culturable bacterial associates in order to interrogate their relationship with D. discoideum. To do this, we isolated over 250 D. discoideum fruiting body samples from soil and deer feces at Mountain Lake Biological Station. In one-third of the wild D. discoideum we tested, one to six bacterial species were found per fruiting body sorus (spore mass) for a total of 174 bacterial isolates. The remaining two-thirds of D. discoideum fruiting body samples did not contain culturable bacteria, as is thought to be the norm. A majority (71.4%) of the unique bacterial haplotypes are in Proteobacteria. The rest are in either Actinobacteria, Bacteriodetes, or Firmicutes. The highest bacterial diversity was found in D. discoideum fruiting bodies originating from deer feces (27 OTUs), greater than either of those originating in shallow (11 OTUs) or in deep soil (4 OTUs). Rarefaction curves and the Chao1 estimator for species richness indicated the diversity in any substrate was not fully sampled, but for soil it came close. A majority of the D. discoideum-associated bacteria were edible by D. discoideum and supported its growth (75.2% for feces and 81.8% for soil habitats). However, we found several bacteria genera were able to evade phagocytosis and persist in D. discoideum cells through one or more social cycles. This study focuses not on the entire D. discoideum microbiome, but on the culturable subset of bacteria that have important eukaryote interactions as prey, symbionts, or pathogens. These eukaryote and bacteria interactions may provide fertile ground for investigations of bacteria using amoebas to gain an initial foothold in eukaryotes and of the origins of symbiosis and simple microbiomes.